Effects of sesamin on the biosynthesis of chondroitin sulfate proteoglycans in human articular chondrocytes in primary culture - Pothacharoen P. (Kluwer Academic Publishers, 2014)
Osteoarthritis (OA) is a degenerative joint disease that progressively causes a loss of joint functions and the impaired quality of life. The most significant event in OA is a high degree of degradation of articular cartilage accompanied by the loss of chondroitin sulfate-proteoglycans (CS-PGs). Recently, the chondroprotective effects of sesamin, the naturally occurring substance found in sesame seeds, have been proved in a rat model of papain-induced osteoarthritis. We hypothesized that sesamin may be associated with possible promotion of the biosynthesis of CS-PGs in human articular chondrocytes. The aim of the study was to investigate the effects of sesamin on the major CS-PG biosynthesis in primary human chondrocyte. The effects of sesamin on the gene expression of the PG core and the CS biosynthetic enzymes as well as on the secretion of glycosaminoglycans (GAGs) in monolayer and pellet culture systems of articular chondrocytes. Sesamin significantly increased the GAGs content both in culture medium and pellet matrix. Real-time-quantitative PCR showed that sesamin promoted the expression of the genes encoding the core protein (ACAN) of the major CS-PG aggrecan and the biosynthetic enzymes (XYLT1, XYLT2, CHSY1 and CHPF) required for the synthesis of CS-GAG side chains. Safranin-O staining of sesamin treated chondrocyte pellet section confirmed the high degree of GAG accumulation. These results were correlated with an increased level of secreted GAGs in the media of cultured articular chondrocytes in both culture systems. Thus, sesamin would provide a potential therapeutic strategy for treating OA patients. © 2013 Springer Science+Business Media.